Library and IT mergers [ - Mitchell, Eleanor; Watstein, Sarah Barbara (Reference services review, 2007)
Part of this issue focuses on the theme of Library/IT mergers. Four articles and an introduction provide details of different approaches to Library/IT mergers. The success of academic libraries and IT services has more to do with the quality of leadership and professional commitment to service than it does with the question of whether these two academic units should merge